High Cellobiase and Xylanase Production by Sclerotium rolfsii UV-8 Mutant in Submerged Culture - Sadana, J. C. (1980)
Sclerotium rolfsii UV-8 mutant secretes high levels of cellobiase and xylanase in addition to having high cellulase production. The apparent K(m) and V(max) of cellobiase (grown in NM-2 + 2% corn steep liquor medium) with cellobiose as a substrate were 5.6 mM and 22.2 μmol of glucose liberated per min per ml of culture filtrate, respectively. The addition of 2% corn steep liquor to NM-2 medium increased endo-β-glucanase, cellobiase, and xylanase yields by approximately 1.5-fold.